A revision of the Venezuelan Anoles I: A new Anolis species from the Andes of Venezuela with the redescription of Anolis jacare Boulenger 1903 (Reptilia: Polychrotidae) and the clarification of the status of Anolis nigropunctatus Williams 1974 - Ugueto, Gabriel N.; Fuenmayor, Gilson Rivas; Barros, Tito; Sánchez-Pacheco, Santiago J.; García-Pérez, Juan E. (Zootaxa, 2007)
Anolis nigropunctatus is herein synonymized with Anolis jacare. We redescribe A. jacare on the basis of 40 specimens from Trujillo, Mérida and Táchira states in Venezuela as well as from Norte De Santander in Colombia, thus greatly expanding the known distribution of the species. We describe A. anatoloros n. sp., a new species of Anolis lizard from the Andes of Venezuela that is closely related to A. jacare. This species inhabits the premontane wet forests of the eastern Andean piedmont in the states of Barinas, Portuguesa and Trujillo and is likely a vicariant of A. jacare. The two species differ in dewlap and body coloration as well as in certain details of the head squamation. A. anatoloros sp. nov. is characterized by a turquoise green dewlap, large scales bordering the inner margin of the supraciliar series, usually a higher number of suboculars in contact with supralabials and large scales around the interparietal.